Molecular identification and characterization of two rubber dandelion amalgaviruses - Debat, Humberto Julio; Zinan Luo; Iaffaldano, Brian J.; Xiaofeng, Zhuang; Cornish, Katrina (2018)
The Amalgaviridae family is composed of persistent viruses that share the genome architecture of Totiviridae and gene evolutionary resemblance to Partitiviridae. A single Amalgavirus genus has been assigned to this family, presenting only four recognized species, corresponding to plant infecting viruses with dsRNA monopartite genomes of ca. 3.4 kb. Here, we present the genomic identification and characterization of two novel viruses detected in rubber dandelion (Taraxacum kok-saghyz). The sequenced isolates presented genomes of 3,409 and 3,413 nt long, including two partially overlapping ORFs encoding a putative coat protein and an RNA-dependent RNA polymerase (RdRP). Phylogenetic insights based on the detected virus sequences suggest them to be members of two new species within the Amalgavirus genus. Multiple independent RNAseq data suggest that the identified viruses have a dynamic distribution and low relative RNA levels in infected plants. Virus presence was not associated with any apparent symptoms on the plant hosts. We propose the names rubber dandelion latent virus 1 & 2 to the detected amalgaviruses; the first viruses to be associated to this emergent and sustainable natural rubber crop.